2013
DOI: 10.1148/radiol.12121181
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Cartilaginous Endplates in Human Intervertebral Disks with Ultrashort Echo Time MR Imaging

Abstract: Purpose:To image human disk-bone specimens by using conventional spin-echo (SE) and ultrashort echo time (TE) techniques, to describe the morphology at magnetic resonance (MR) imaging, and to identify tissue components contributing to high signal intensity near the cartilaginous endplates (CEPs). Materials and Methods:This study was exempt from institutional review board approval, and informed consent was not required. Five cadaveric lumbar spines (mean age, 61 years 6 11) were prepared into six sample types c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 35 publications
1
35
1
Order By: Relevance
“…In addition, histology was performed which confirmed that the MRI FLASH sequence successfully detected the CEP and provided an accurate measurement of CEP thickness. Our MRI FLASH microstructural observations are consistent with recent ultrashort echo time MR imaging of uncalcified and calcified CEP [37] although that study did not measure CEP thickness. The CEP thickness measured in the mid-sagittal plane both ex vivo and in vivo gave similar results, showing no effect of level, but the CEP becomes thinner toward the center of the disc.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, histology was performed which confirmed that the MRI FLASH sequence successfully detected the CEP and provided an accurate measurement of CEP thickness. Our MRI FLASH microstructural observations are consistent with recent ultrashort echo time MR imaging of uncalcified and calcified CEP [37] although that study did not measure CEP thickness. The CEP thickness measured in the mid-sagittal plane both ex vivo and in vivo gave similar results, showing no effect of level, but the CEP becomes thinner toward the center of the disc.…”
Section: Discussionsupporting
confidence: 90%
“…11,41 Recent studies indicated that new sequences, for example, ultrashort echo time and fast low-angle shot can enhance visualization of the endplate's anatomic details. 4244 If these sequences can also demonstrate sensitivity to variation in collagen content, then our findings suggest that such sequences could enable noninvasive assessment of endplate biomechanical properties, which might prove useful for prognostic purposes.…”
Section: Discussionmentioning
confidence: 85%
“…For example, endplate boundary conditions obtained from magnetic resonance imaging (MRI)-based FE modeling of IVDs have aided predictions of failure patterns made with high-resolution peripheral QCT (HR-pQCT)-based FE models (Maquer et al, 2015). MRI protocols that resolve the condition of the IVD and, separately, the cartilaginous endplate (Bae et al, 2013; Fields et al, 2015), may be particularly advantageous for estimating load transfer between IVD and vertebra.…”
Section: Discussionmentioning
confidence: 99%